Application of GPS devices to longitudinal analysis on game and training data - Neville, J.; Rowlands, D.; Wixted, A.; James, D. (Procedia Engineering, 2012)
In elite level team sport, the application of longitudinal data analysis is often overlooked due to the tools and techniques required for processing large quantities of data. The research presented in this paper explores the information available to coaches and players when looking at data taken from an entire first grade Australian Rules Football team for a full non-premiership season. Specifically this paper explores the relationship between training and game demand on an individual level as well as exploring the relative demand on different player field positions. The hardware used in this research was the GPSports SPI Inertial tracking unit. This device contained a GPS unit tracking at 5 Hz providing the latitudinal and longitudinal position of the players. This GPS information was then extracted in order to reconstruct the speeds of the athlete throughout a game. This research found strong correlations between the overall intensities of the training sessions and the physical demand of first grade games. It also identified small differences in the demand of different on field positions.